Analisis Dinamis Tegangan, Regangan, dan Displacement Badan Perahu Jaloe Kayoh Berbahan Material Komposit dengan Pembebanan Merata Menggunakan Metode Elemen Hingga - Iskandar Hasanuddin; Akram Akram; Adhitya Pahlefi (Jurnal Teknik Mesin Unsyiah, 2018)
Composite material is a combination of two or more different materials between resin and fiber. The characteristic of this material is that it has a high level of corrosion resistance. This study aims to analyze the strength and durability of jaloe kayoh made from Jute fiber polyster composite materials. Dynamic analysis on jaloe kayoh is done through simulation or modeling using CAE-based software with the Finite Element Method (FEM), using dynamic-implicit conditions. The parameters examined include stress, strain and displacement values for uniform loading on the entire boat body with a minimum load of 600 N and a maximum load of 3000 N accompanied by amplitude. Variations in material applied to the jaloe kayoh include jute, jute glass, jute glass jute, and fiberglass. From the simulation results on the loading of 3000 N the largest maximum stress obtained by jute glass jute material with a value of 1,707×106 Pa, the largest maximum strain by jute material with a value of 2,721×10-5, and the largest maximum displacement by jute material with a value of 1,400×10-5 m. Then the results of the study showed that the four composite materials were categorized as good to be applied as the main materials for the body of the jaloe kayoh.